Taxonomy and abundance of shipworms (Mollusca, Pelycypoda Teredinidae) in a mangrove plantation in New Buswang, Kalibo, Aklan. - Sumbang, Kristine A.
The Teredinidae (shipworms) are wood-boring bivalves having a worm-like body with shells at the anterior part and excurrent and incurrent siphons at the posterior part. They are destructive to wooden structures exposed in water but they are considered as one of the major delicacies in Aklan nowadays. This study determined the species of shipworm found in New Buswang, Kalibo, Aklan since there is no existing literature on identification of species in the area. This also determined the effect of tidal height and water movement to the abundance of shipworm at different tidal zones of the mangrove plantation from July 2006 to January 2007 to provide information on the best place to culture shipworm. NIne logs were exposed in each of the 3 tidal zones. Site 1 is in the low tidal zone, site 2 in the middle tidal zone and site 3 in the high tidal zone. Three logs were harvested in each sites for the first sampling (September 2006), the second sampling (November 2006) and the third sampling (January 2007). The species of shipworm found in New Buswang, Kalibo, Aklan is Teredo navalis. More and bigger shipworms were also harvested in the high tidal zone since it was near the source of water and logs were exposed longer to water, thus indicating that submergence to water and stronger water movement are the factors that contribute to the abundance of shipworm in a certain area.